The culture of theology - Webster, John, 1955-2016; Davidson, Ivor J.; McCray, Alden C. (Grand Rapids,MI Baker Academic, 2019)
This outstanding work offers a short account of the nature of Christian theology. In a series of six lectures, John Webster explores the privilege of thinking and speaking of God in light of "the staggering good news of Jesus Christ." How might faith approach that task? Webster proposes that we do theology well when we recognize the gospel as the most important reality. He considers the significance of church, Bible, and tradition as foundational to the unique "cultural world" the gospel brings into being, and he explores the challenges as well as the joys of inhabiting that sphere. Theology has particular responsibilities: in its academic conversations, in its self-criticism, and in its spiritual and moral life; at the heart of its calling lies prayer. Webster's exposition, here available in book form for the first time, is accompanied by an introduction by his close colleague, Ivor J. Davidson, who was involved in the original lecture series and discussed the material extensively with him.
Introduction / Ivor J. Davidson -- Culture: the shape of theological practice -- Texts: scripture, reading, and the rhetoric of theology -- Traditions: theology and the public covenant -- Conversations: engaging difference -- Criticism: revelation and disturbance -- Habits: cultivating the theologian's soul.
Includes bibliographical references (pages 149-156) and indexes.
Keywords: Webster, John, -- 1955-2016 -- Influence; Theology; Theology -- Christianity; Religion and culture; Theology, Doctrinal; Theology -- Methodology -- 20th century; Theology of religions (Christian theology); Theology -- Philosophy; Theology -- Research; Theology -- Social aspects